Traditional fish processing in Odisha, India - Taranisen Panda; Nirlipta Mishra; Shaik Rahimuddin; Bikram K. Pradhan; Raj B. Mohanty (Journal of Fisheries, 2022)
The present study documents the traditional fish drying techniques used by the fisher folk communities of Bhadrak district, Odisha, India. Information on local knowledge and the use of different fish drying methods within the study area was collected from 72 fisher folk through semi-structured questionnaires, free interviews, informal conversations and direct observations. The results showed that sun drying was the most extensively used method for fish preservation. About 19.4% of the informants preferred to spread the fishes directly on earth, 34.8% on the mat, 5.5% on palm leaves, 29.2% over bamboo bars and 11.2% followed interlocking of snouts/jaws on bamboo sticks. Almost all the fish drying devices are handmade with bamboo, wooden pole and sometimes nylon threads following traditional technologies. The quality of the dry fish could be improved by educating fishermen on hygiene, sanitation, use of good water quality and raw materials for processing. In this context, the low-cost solar dryer can be constructed by using locally available materials, thus preventing contamination and dependence on weather conditions. The dry fish production can play a crucial role in socio-economic upliftment, employment generation and poverty alleviation particularly to women as they depend on it directly for their livelihoods.